Pemulihan Trauma pada Anak Korban Bencana dalam Perspektif Islam (Studi Kasus Bencana Gunung Sinabung di Desa Guru Kinayan, Kecamatan Payung, Kabupaten Karo, Sumatera Utara) - Faisal Habib Lubis (Universitas Islam Negeri Sumatera Utara Medan, 2021)
ABSTRACT The problem that is currently happening in Indonesia is the occurrence of various disasters, ranging from landslides, floods, earthquakes, tsunamis to the eruption of Mount Merapi with a fairly high potential. The Mount Sinabung disaster, which is currently on alert status, does not yet have a comprehensive management system for the protection and handling of children in particular. Children are a group of people who are vulnerable to trauma or psychological disorders requiring problem solving, events that are experienced by a person and are not able to be anticipated can cause psychological disturbances for that person. This change in social phenomena requires a study and trauma recovery to restore belief in religion. Religion becomes a choice and a reference to overcome the conflicts that occur within him. Researchers feel it is important to create a disaster trauma recovery method based on an Islamic perspective as a form and response to the social conditions of the victims to be able to reduce trauma as a result of the disaster. Thus the question arises, namely what steps are taken in trauma recovery in children based on an Islamic perspective.This paper explores the concept of Islam as a religion that contains high spiritual values capable of solving human psychological problems in facing trials and overcoming difficulties in life. Keywords: Trauma Healing, Children, Islamic Perspective.